Topology and Control Strategy for Input-series and Output-series Cascaded Soft-switching BOOST Converter - ZHU Qiliang; CHEN Yifeng; ZHANG Honghao (Kongzhi Yu Xinxi Jishu)
To meet the demand of higher voltage for power converters, an input-series and output-series cascaded soft-switching Boost topology was proposed. This topology is composed of two identical Boost converters, which can half the voltage stress of power devices and in which higher cost-effective and lower voltage power devices can be used. Then a ZVT resonant circuit was introduced to reduce the loss of the power devices, improve the efficiency of the converter and lower the EMI. The control strategy for neutral voltage balance was also introduced to strongly keep the half voltage stress for those power devices. Finally, Matlab simulations and experimental prototype were built to verify the novel topology and control strategy.